MARCH5 restores endothelial cell function against ischaemic/hypoxia injury via Akt/eNOS pathway. Issue 7 (21st February 2021) - Lei, Wenhua; Li, Junli; Li, Changming; Chen, Li; Huang, Fangyang; Xiao, Dan; Zhang, Jialiang; Zhao, Jiahao; Li, Guoyong; Qu, Tianyi; Zhou, Hao; Liao, Yanbiao; et al.
Abstract: MARCH5 is a critical regulator of mitochondrial dynamics, apoptosis and mitophagy. However, its role in cardiovascular system remains poorly understood. This study aimed to investigate the role of MARCH5 in endothelial cell (ECs) injury and the involvement of the Akt/eNOS signalling pathway in this process. Rat models of myocardial infarction (MI) and human cardiac microvascular endothelial cells (HCMECs) exposed to hypoxia (1% O2 ) were used in this study. MARCH5 expression was significantly reduced in ECs of MI hearts and ECs exposed to hypoxia. Hypoxia inhibited the proliferation, migration and tube formation of ECs, and these effects were aggravated by knockdown of MARCH5 but antagonized by overexpressed MARCH5. Overexpression of MARCH5 increased nitric oxide (NO) content, p‐eNOS and p‐Akt, while MARCH5 knockdown exerted the opposite effects. The protective effects mediated by MARCH5 overexpression on ECs could be inhibited by eNOS inhibitor L‐NAME and Akt inhibitor LY294002. In conclusion, these results indicated that MARCH5 acts as a protective factor in ischaemia/hypoxia‐induced ECs injury partially through Akt/eNOS pathway.